Expression profiling of development related genes in rice plants ectopically expressing AtTOR. (2nd September 2017) - Bakshi, Achala; Moin, Mazahar; Datla, Raju; Kirti, P. B.
ABSTRACT: Expression analysis of genes associated with development at different growth stages such as shoot apical meristem (SAM), root apical meristem (RAM), shoot and root tissues 10 DAG, flowers and grains of 2 high expression transgenic lines of rice ectopically expressing AtTOR revealed the involvement of AtTOR in transcriptional regulation of these genes. We have observed that in the SAM of these 2 selected lines, TR-2.24 and TR-15.1, OsFON 1 and OsFON 4 (orthologs of AtCLV 1 and AtCLV 3, respectively), OsKNOX 2, OsKNOX 3 and OsWOX 3 became upregulated. The upregulation of OsFON 1 and OsFON 4 is likely to be involved in the maintenance of effective meristem size of the inflorescence and phyllotaxis. The grains and spikes of transgenic plants exhibited enhanced transcript levels of OsMADS 1, OsMADS 6, and OsMADS 29 further implicating the role of TOR in modulating the expression of the genes in rice grain formation and development. Moreover, the upregulation of auxin transporter, PIN 1c in RAM and roots derived from seedlings 10 DAG showed the involvement of TOR in root development. The seeds of 2 high expression lines also showed increased expression of OSE 2 and GAMYB transcription factors involved in seed development. In summary, the present study, by heterologous expression of AtTOR in rice, demonstrated the involvement of TOR in regulating genes involved in various growth and developmental stages of rice plant and also in photosynthesis, productivity related functions and water-use efficiency.